A Mixed Methods Study of Self-Efficacy, the Sources of Self-Efficacy, and Teaching Experience - Gale, Jessica; Alemdar, Meltem; Cappelli, Christopher; Morris, David (Frontiers in Education, 2021)
Although teaching self-efficacy is associated with many benefits for teachers and students, little is known about how teachers develop a sense of efficacy in the early years of their careers. Drawing on survey (N = 179) and interview (N = 10) data, this study investigates the sources of self-efficacy in a national sample of teachers who participated in the Noyce program. All teachers completed an online survey that included both the Teacher Sense of Efficacy Instrument and open-ended items prompting them to reflect on the sources of their self-efficacy. Ten teachers participated in semi-structured follow-up interviews. Enactive mastery experiences were the most common source of self-efficacy identified by teachers, followed by social persuasions and vicarious experiences. Physiological and affective states were identified infrequently and more often related to negative experiences that lowered self-efficacy than to positive experiences. Beginning teachers identified more negative enactive experiences than either Novice (2–3 years experiences) or Career teachers. In interviews, teachers described how the sources combined or interacted to influence their self-efficacy. Findings contribute to better understandings of the sources of self-efficacy with implications for how best to support teachers at different stages of their careers.